2023
DOI: 10.3390/pharmaceutics15030747
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Naringin-Loaded Fibers for Preventing Scar Formation during Wound Healing

Abstract: Hypertrophic scars (HTSs) are aberrant structures that develop where skin is injured complexly and represent the result of a chronic inflammation as a healing response. To date, there is no satisfactory prevention option for HTSs, which is due to the complexity of multiple mechanisms behind the formation of these structures. The present work aimed to propose Biofiber (Biodegradable fiber), an advanced textured electrospun dressing, as a suitable solution for HTS formation in complex wounds. Biofiber has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
(54 reference statements)
1
9
0
Order By: Relevance
“…The combination of these two polymers as copolymers or polymer blends enables the production of materials with the desired characteristics of both constituent elements. PLA is renowned for its stability and robustness, while PCL is widely used in wound healing products due to its intrinsic tissue adhesion and excellent conformability [3,17,18,50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of these two polymers as copolymers or polymer blends enables the production of materials with the desired characteristics of both constituent elements. PLA is renowned for its stability and robustness, while PCL is widely used in wound healing products due to its intrinsic tissue adhesion and excellent conformability [3,17,18,50].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the circular pattern was made after considering earlier research findings, which had shown its effectiveness in enhancing the mechanical characteristics of the dressing and its ability to conform well to the contours of the body's surface. Additionally, this particular and bright texture contributes to wound transpiration and modulates the exudate [3,36]. To further enhance breathability, the electrospinning process was designed to control the pore size and distribution.…”
Section: Morphology Characterization By Scanning Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The electrospinning technique allows for the production of nanofibers with a higher surface area and dissolution rate, which can improve drug release [ 42 ]. The larger surface area to volume ratio of electrospun nanofibers enables them to load a large amount of drug, making them ideal for drug delivery applications [ 43 , 44 , 45 ].…”
Section: Nanomaterials Used In Wound Dressingmentioning
confidence: 99%
“…This study provides a new method for absorbing exudate and draining sweat. Erika Marie Tottoli et al [18] prepared a textured bandage of PLA-PCL, which achieves an optimal balance of moisture retention, flexibility, and skin-fitting properties and provides technical support for subsequent studies of textured dressings.…”
Section: Exudate Absorptionmentioning
confidence: 99%